The New Era of Biologics in Atopic Dermatitis: A Review - Simon Schneider; Linda Li; Alexander Zink (Dermatology Practical & Conceptual, 2021)
Atopic dermatitis (AD) is a prevalent inflammatory skin disorder affecting all ages and ethnic groups. The age-dependent varying appearance and extent of pruritic lesions are accompanied by distinct individual suffering, highlighting the importance of effective treatment options. Over the past years, systemic drugs have considerably extended therapeutic approaches of patients with moderate to severe AD, in particular, new biologics, most notably dupilumab has appeared as major breakthrough. In addition to monoclonal blockade of IL-4 and IL-13 pathway, more cytokines have been found to play a substantial role in AD pathogenesis, presenting potential targets for new therapy options.